2011
DOI: 10.1016/j.bbadis.2010.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial defect and PGC-1α dysfunction in parkin-associated familial Parkinson's disease

Abstract: Mutations in the parkin gene are expected to play an essential role in autosomal recessive Parkinson's disease. Recent studies have established an impact of parkin mutations on mitochondrial function and autophagy. In primary skin fibroblasts from two patients affected by an early onset Parkinson's disease, we identified a hitherto unreported compound heterozygous mutation del exon2-3/del exon3 in the parkin gene, leading to the complete loss of the full-length protein. In both patients, but not in their heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 83 publications
14
102
3
Order By: Relevance
“…Absorbance change was recorded at 450 nm using a Victor X3 Multilabel Plate Readers. Catalase activity was assayed by monitoring spectrophotometrically the rate of decomposition of H 2 O 2 at 240 nm as previously described (Pacelli et al, 2011).…”
Section: Anti-oxidant Enzyme Activitiesmentioning
confidence: 99%
“…Absorbance change was recorded at 450 nm using a Victor X3 Multilabel Plate Readers. Catalase activity was assayed by monitoring spectrophotometrically the rate of decomposition of H 2 O 2 at 240 nm as previously described (Pacelli et al, 2011).…”
Section: Anti-oxidant Enzyme Activitiesmentioning
confidence: 99%
“…This would resolve the apparent contradictions in some of these models and may explain why the rescue of PINK1-deficiency phenotypes by parkin in flies is only a partial effect. This may also be related to observations of changes in PGC1a-responsive genes in fibroblasts from parkin mutation carriers (Pacelli et al 2011). Finally, if it is correct that there are many functional locations of parkin, we might surmise that the apparent lack of specificity of the protein may have evolved from a need to coordinate PINK1, Parkin, and DJ-1…”
Section: Biochemical Function In the Pink1/parkin Pathwaymentioning
confidence: 99%
“…Investigations on transfected cell cultures has, however, provided evidence that parkin can also up-or down-regulate the expression of different genes [29]. Extensive investigation in the authors' laboratory in primary cultures of fibroblasts from patient's skin biopsies have shown that different mutations of PARK2, in independent patients affected by autosomal recessive PD, resulted in depression of mitochondrial respiratory chain enzymes, in particular complex I, inhibition of the mitochondrial respiratory activity and ATP production [30]. These effects were associated with defect in the PGC1□ mastered transcription cascade of mitochondrial respiratory proteins [30].…”
Section: How Familial Cases Of Pd Help To Identify Pathogenetic Mechamentioning
confidence: 99%
“…Extensive investigation in the authors' laboratory in primary cultures of fibroblasts from patient's skin biopsies have shown that different mutations of PARK2, in independent patients affected by autosomal recessive PD, resulted in depression of mitochondrial respiratory chain enzymes, in particular complex I, inhibition of the mitochondrial respiratory activity and ATP production [30]. These effects were associated with defect in the PGC1□ mastered transcription cascade of mitochondrial respiratory proteins [30]. Pathogenetic mutations in PARK6, coding for PINK1 serine/threonine kinase, represent the second most common cause of autosomal recessive PD.…”
Section: How Familial Cases Of Pd Help To Identify Pathogenetic Mechamentioning
confidence: 99%
See 1 more Smart Citation